How to Build Your Own Morse Code Practice Generator. - Kahaner, Larry (Smithsonian)
The article focuses on number of ham operators is declining globally and its growing in the as is Morse code, by all accounts. It mentions Federal Communications Commission, which licenses all U.S. hams, dropped its requirement that beginner operators be proficient in Morse code. It also mentions British inventors William Cooke and Charles Wheatstone had used an electromagnet to create the first telegraph receiver, patented in 1837 and languages alike boosts neuroplasticity in similar ways.